Factors associated with home visits by volunteer community health workers to implement a home-fortification intervention in Bangladesh: a multilevel analysis - Sarma, Haribondhu (Public Health Nutr, 2021)
OBJECTIVE: BRAC, an international development organization based in Bangladesh, engages community health workers called Shasthya Shebikas (SS) to implement home fortification of foods with micronutrient powders (MNP). We identified factors associated with home visits by SS, at different levels of the BRAC programme-delivery hierarchy, to implement home-fortification interventions. DESIGN: We conducted a cross-sectional survey, semi-structured interviews, and collected programme-related data from sub-districts included in the caregiver survey of BRAC’s home-fortification programme and performed multilevel logistic regression modelling to investigate factors associated with home visits by SS. SETTINGS: Sixty-eight sub-districts in Bangladesh. PARTICIPANTS: Caregivers of children aged 6–59 months (n 1408) and BRAC’s SS (n 201). RESULTS: Households with older children (0·55; 0·42, 0·72; P < 0·001) and located >300 m from the SS’s house (0·67; 0·50, 0·89; P = 0·006) were less likely to have been visited by the SS, whereas those with caregivers who had ≥5 years of schooling (1·53; 1·10, 2·12; P = 0·011) were more likely to have been visited by the SS (adjusted OR; 95 % CI). Households in the catchment area of older SS aged >50 years (0·44; 0·21, 0·90; P = 0·025) were less likely to have been visited by the SS, whereas those with SS who received incentives of >800 BDT (3·00; 1·58, 5·58; P = 0·001) were more likely to have been visited by the SS (adjusted OR; 95 % CI). CONCLUSIONS: The number of home visits is a function of the characteristics of SS, factors that characterize the households they serve and characteristics of their organizational context, particularly to implement home fortification of foods with MNP.